The Impact of the Techniques and Tactics Appropriate by the Athletes in Phase Triple Jump and Their Relationships with the Finale Results - Zerf, Mohammed; Mokkedes, Moulay Idris; Bengoua, Ali; Bendahmane, Mohammed Nasreddine; Guebli, Abdelkader (My University, 2015)
The purposes of this study were to describe and compare the techniques used by elite world triple jumper and the Algerian elite team to determine the impact of distribution modality phases allowing the elite to exceeds 17-meter. Our subjects were two world elite 2009 and two Algerian national elite 2013. In the lack of new technology Modern measuring instruments kinematics or kinetics, our study based in measure of the Phase distribution ratio as measure of Stride length Jump distance. That literature review two schools, the Russian technique (which emphasizes the hop phase) and the Polish technique (which emphasizes the jump phase). Our aims for this study are: Are there any statistically significant differences between the results of the samples in the distance achieved? Are there any statistically significant differences between practical Ratio relative distances (world 2009-national 2013)? Are there any statistically significant differences between Stride length phase distances (world 2009-national 2013)? For that, we have chosen the analysis of variance and correlation of the distances achieved in each of the phases with the official distance of jumper and “T” student to compare implementation distribution of phases (hop, step and jump) with the results accuses. Based on the practices and weaknesses of elites in practice, we confirm: (1) All the samples practice the Russian technique as model in the distribution of the phase ratio; (2) The problem of our elites is in the hop phase distribution and its relationship with other phases; (3) Improve achieve horizontal vertical velocity in hop phase as solution.
Keywords: The ratio phase; techniques; tactics appropriate; triple jump